The wheels on the bus - Dean, James; Dean, James, 1957- (New York : Harper, 2013)
Pete the cat's school day is recounted in this twist on the classic song.
Keywords: Children's songs, English -- United States -- Texts; Cats -- Songs and music -- Texts; School buses -- Songs and music -- Texts; Schools -- Songs and music -- Texts; Songs